Media: Library Based Information Search and Research - Raguram, S. (Foundation for Library Awareness, Jaffna, 2016)
The social, economic, political and cultural backgrounds of individuals and communities determine the way the communication is perceived by them. This can be seen as a natural mechanism where people shape the substance of the very communication they are involved in and receive from the media. People never absorb the stories provided by the media in their raw forms. Consumption of media is often influenced by traditions, class, ethnicity, gender and ideology of the community. Any news story that is consciously created to give a particular meaning to the public may be accepted partially, absorbed in the way suited to them or rejected by the people. Media reinforcement leads to deep peruses at a community level. This situation made media organizations extremely realize their roles. Media are in a position to work hard beyond their normal routine in which they collect and manage information for their publications. The audience with self-interest and able to analyze the information approach the media content very critically. This phenomenon was pointed out by many researchers. Globalization impacted the professional development of media in many ways. The general platforms expect the journalists to gather information with pre-planning and in a deeper manner.